Secreted Frizzled-Related Protein 1 as a Biomarker against Incomplete Age-Related Lobular Involution and Microcalcifications’ Development - Clemenceau, Alisson (Cancers (Basel), 2020)
SIMPLE SUMMARY: Age-related lobular involution, a physiological breast atrophy, is a natural weapon against breast cancer development. Microcalcifications, which are present in 90% of diagnosed ductal carcinoma in situ, are associated with tumor invasiveness and aggressivity, but their impact on lobular involution remains unknown. In this study, we highlighted two predictive models for incomplete lobular involution and microcalcifications development. By identifying women at high risk of incomplete lobular involution, we hope to better prevent breast cancer development and so, to reduce late diagnostics. By preventing microcalcifications development, we will offer a new preventive tool for women younger than 50 years old who do not have access to mammography. We also identified two distinct inflammatory profiles associated with age-related lobular involution in parous and nulliparous women. These results warrant further investigation and could be crucial in personalized therapy development against breast cancer. ABSTRACT: As a downregulator of the Wnt signaling pathway, SFRP1 is involved in several components of the age-related lobular involution process such as inflammation, apoptosis, and adipogenesis. Because microcalcifications are associated with inflammation, we aimed to demystify the cross talk between SFRP1, inflammatory markers, and microcalcifications by assessing SFRP1 expression (immunohistochemistry) in a cohort of 162 women with different degrees of lobular involution. SFRP1 expression was inversely associated with the degree of lobular involution (OR = 0.84; p-value < 0.01). SFRP1 expression, age at mastectomy, and waist circumference taken together predicted the degree of lobular involution (AUC = 78.1). This predictive model was best in patients with microcalcifications (AUC = 81.1) and in parous women (AUC = 87.8). SFRP1 expression was correlated with leptin (rho = 0.32), TNF-α (rho = 0.21), and IL-6 (rho = 0.21) expression by epithelial cells (all p-values <0.001). SFRP1 expression was lower in nulliparous women with involuted breast tissue compared with parous women with involuted breast tissue (Δmean = −2.31; p-value < 0.01) and was higher in nulliparous women with microcalcifications compared with nulliparous women without microcalcifications (Δmean = 2.4; p-value < 0.05). In this study, we highlighted two SFRP1-based predictive models for incomplete lobular involution and the development of microcalcifications and identified two distinct inflammatory profiles associated with age-related lobular involution in parous and nulliparous women.